Where food safety meets nutrition outcomes in livestock and fish value chains: a conceptual approach - Häsler, Barbara; Domínguez Salas, Paula; Fornace, K.; Garza, M.; Grace, Delia; Rushton, Jonathan (Springer, 2017)
There is increasing interest in the links between food safety and nutrition. Animal-source foods contribute to fulfilling important micronutrient requirements by supplying vitamin B12, high quality protein, iron, zinc, vitamin A of high bioavailability, riboflavin and calcium. However, high meat and dairy consumption may raise health concerns related to the risk of non-communicable diseases and food safety, especially if upscaling of livestock and fish value chains does not follow recommended hygiene and biosecurity practices. A recent report by the World Health Organisation indicates that food-borne diseases from animal-source foods constitutes an important health burden worldwide. Only a few studies explore nutrition outcomes and food-borne diseases simultaneously and integrative approaches may be difficult due to limited understanding of disciplinary paradigms. Here we propose a conceptual approach to integrate food safety and nutrition assessments in livestock and fish value chains combining knowledge from food sciences, public health, nutrition and economics. It offers six analytical dimensions with explanations of key disciplinary paradigms and methodological characteristics that can cause pitfalls for integration and provides recommendations for joint assessments. The insights arising from this work on methodology for interdisciplinary research can assist those who engage in collaboration to integrate food safety and nutrition research in livestock and fish value chains.